Treating top management team conflicts through employee voice for reducing intentions to quit: moderating role of union instrumentality. Issue 2 (15th October 2021) - Chaudhry, Naveed Iqbal; Roomi, Muhammad Azam; Eugien, Marium; Chaudhry, Javed Iqbal
Abstract : Purpose: This study aims to explain the relationship of employee voice and turnover intention with the mediating role of top management team (TMT) conflicts. Moreover, this study also aims to find the moderating influence of union instrumentality among employee voice and TMT conflicts. Design/methodology/approach: The study was conducted by using a quantitative approach and data was collected from 300 employees of the manufacturing sector of Pakistan through questionnaires. Data were analyzed by applying different statistical tools and tests through SPSS-21 and AMOS. Findings: Results demonstrate that employee voice has a significant negative impact on employee turnover intention; TMT conflicts significantly mediate employee voice and intention to quit. However, union instrumentality is only initiated to moderate the relationship between employee voice and cognitive conflict. Research limitations/implications: This research focuses on the manufacturing sector and data have been collected from manufacturing firms situated in Gujranwala, Pakistan only. Moreover, the sample size of the study is also small. Therefore, the current study is an addition to the knowledge and understanding of the studied variables. Practical implications: This study is of great use for managerial level employees because the adequate implication of employee voice can reduce turnover intention. Originality/value: This study aims to add value to the existing exit-voice theory and discuss the internal organizational factors that generate quitting intentions. Moreover, it provides insights about union instrumentality and its significant role as a moderator and the significant mediating role between employee voice and intention to quit paving new ways for future researchers.